Ethical Issues in Researching Higher Education Teaching and Learning - Jennie Golding; Amanda Ince (Encyclopedia)
Higher education here is taken to be education beyond school level: often at an institution (a university) that has degree-awarding powers, though some programmes may lead to a diploma, certificate or other award or qualification. Nomenclature around “research” in the associated teaching and learning is contested: professional enquiry, scholarship of teaching and learning, pedagogical research… are some of the terms used. Authors discuss and distinguish such terms. An ethical issue is a circumstance in which a moral conflict arises or is implicit and should be resolved in a morally acceptable way. These include privacy, informed consent, insider research and power relationships within higher education research; there are also fluid challenges around the use of digital contributions. Authors present a narrative exegesis of work in the associated areas, which authors argue will be of use to universities promoting such research, and of particular interest to two groups of academics wishing to systematically develop their practice in ways that contribute to the field: those on teaching-only contracts, who would also demonstrate their research credentials; and researchers from non-education-cognate fields. Authors identify directions for further work.